ISOLATION AND IDENTIFICATION OF GALLIC ACID FROM POLYALTHIA LONGIFOLIA (SONN.) THAWAITES - SAMPATH M (International Journal of Pharma and Bio Sciences, 2013)
Isolation and purification of bioactive compounds from naturally occurring substance will play a central role in the development and modernization of phytomedicine.The study was carried out to the isolate and simultaneous identification of gallic acid from the Ethanolic Extract of Polyalthia Longifolia (Sonn.) Thawaites leaves (EEPL). The simple, rapid and cost effective Preparative Thin Layer Chromatography (PTLC) was used for the identification and isolation of gallic acid. Rf value of PTLC isolate and reference standard gallic acid was found to be 0.47 and 0.48 respectively. Reverse Phase High Performance Liquid Chromatography (RP-HPLC) fingerprint of PTLC isolate of EEPL also revealed that the presence of gallic acid.